A procura de um jornal público - Silva, Luiz Martins da (2022)
Since when Gutenberg 1 's “bible ” was published, approximately five centuries and a half ago, the press has functioned as a public forum targeted to publicize facts related to the general public interests. This public function has been incorporated, in general terms, by the private sector, even though there been incorporated, in general terms, by the private sector, even though there are many public radio and TV broadcasts sponsored and administered by the State. Different from what can be found in the audiovisual media, there are no public newspapers except for governmental publications, such as the national gazette. Nevertheless, the official press is limited to the so-called legal publicity. On the other hand, publications of the Third Sector (Non-governmental Organizations — NGOs and Social Organizations — SOs) has purpose to have any influence over the press. The main question is why there are no public newspaper? The answers represent a tentative task of “sociological imagination ” to understand what could be a public newspaper or public journalism.